A new 4π(LS)-γ coincidence counter at NCBJ RC POLATOM with TDCR detector in the beta channel. (March 2016) - Ziemek, T.; Jęczmieniowski, A.; Cacko, D.; Broda, R.; Lech, E.
Abstract: A new 4π(LS)-γ coincidence system (TDCRG) was built at the NCBJ RC POLATOM. The counter consists of a TDCR detector in the beta channel and scintillation detector with NaI(Tl) crystal in the gamma channel. The system is equipped with a digital board with FPGA, which records and analyses coincidences in the TDCR detector and coincidences between the beta and gamma channels. The characteristics of the system and a scheme of the FPGA implementation with behavioral simulation are given. The TDCRG counter was validated by activity measurements on 14 C and 60 Co solutions standardized in RC POLATOM using previously validated methods. Highlights: A new 4π(LS)-γ coincidence system (TDCRG) with TDCR detector in the beta channel. The digital board with FPGA implementation by in-house code. Checking of the FPGA module by the behavioral simulation. Validation of the TDCRG counter by 14 C and 60 Co solutions activity measurements.